A Profile of the Academy of Management Member: Comment - Duncan, W. Jack (Academy of Management Journal, 1970)
The article reports the author's opinions regarding the article ?A Profile of the Academy of Management Member,? by Roderick A. Forsgren, published in the March 1969 issue. The author focuses on comparing the data he has collected regarding members of the Academy of Management to that obtained by Forsgren. It is suggested that Forsgren failed to investigate the religious preferences of business professors in his study.